Kinetics of microbial protein production and in vitro digestibility of straw ammoniated and/or supplemented with NPN and protein - SINGH, G P; KLOPENSTEIN, T J (The Indian Journal of Animal Sciences, 2013)
IVDMD, IVOMD and microbial protein synthesis kinetics of untreated wheat straw, untreated wheat straw + urea, 3% ammoniated straw and ammoniated wheat straw + casein were determined using rumen liquor of animal fed corn cob and alfalfa. Supplementation of urea increased the IVDMD and IVOMD significantly (P